CASCAD CONTROL FOR PLANT WITH PARAMETER UNSERTAINTY - O. F. Opeiko (Системный анализ и прикладная информатика)
The cascade control is developed for the case of plant parameters uncertainty. The two loops system is considered with proportionalintegrate (PI) controllers, such the parametric synthesis can be generalized for multi loops systems. The necessary quality of the system is achieved by the correct polynomial’s roots location on a complex plane. The roots location is defined to achieve the low sensitivity of the system to plant’s parameters variations. The multiples numerical examples are presented for developed method, which demonstrate the belonging of polynomials roots to the restricted area of left hand half of complex plane for various multi loops systems.